2006
DOI: 10.1364/ol.31.002260
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity enhancement of fiber Bragg gratings to transverse stress by using microstructural fibers

Abstract: We present simulation and experimental results of fiber Bragg grating responses to transverse stress in microstructure fibers. The grating wavelength shifts and peak splits are studied as a function of external load and fiber orientation. Both simulation and measurement results indicate that the sensitivity of grating sensors to the transverse stress can be enhanced by a factor of eight in a two-hole fiber over that in a standard fiber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 6 publications
(7 reference statements)
0
28
0
Order By: Relevance
“…Fiberoptic sensors based on fiber Bragg gratings [22][23][24][25][26] or long period gratings [27] have been reported for transverse load sensing. In this paper, we demonstrated that the transverse load sensing can be realized by using the proposed bubble-structure micro-cavity.…”
Section: Characterization Of Fiber Tip Micro-cavity Sensorsmentioning
confidence: 99%
“…Fiberoptic sensors based on fiber Bragg gratings [22][23][24][25][26] or long period gratings [27] have been reported for transverse load sensing. In this paper, we demonstrated that the transverse load sensing can be realized by using the proposed bubble-structure micro-cavity.…”
Section: Characterization Of Fiber Tip Micro-cavity Sensorsmentioning
confidence: 99%
“…For instance, FBG incorporated MOF sensors can induce a contra-directional coupling between forward and backward fiber modes through resonant scattering and thus perform very well in strain, pressure and microfluidic refractive index sensing applications [27][28][29][30][31][32]. For instance, C. Martelli et al characterized strain and temperature responses of the FBG on the MOF and showed an increased sensitivity to strain by leaky modes of MOFs which was not presented in conventional fibers [27].…”
Section: Microstructured Optical Fiber Bragg Grating Sensorsmentioning
confidence: 99%
“…For instance, C. Martelli et al characterized strain and temperature responses of the FBG on the MOF and showed an increased sensitivity to strain by leaky modes of MOFs which was not presented in conventional fibers [27]. C. Jewart et al demonstrated that the transverse stress sensitivity of the two-hole fiber could be enhanced by a factor of eight compared with a standard fiber [28]. T. Martynkien et al designed, manufactured, and characterized two kinds of birefringent MOFs.…”
Section: Microstructured Optical Fiber Bragg Grating Sensorsmentioning
confidence: 99%
“…The most straightforward implementation of a mechanically asymmetric birefringent optical fiber is the side-hole fiber (with elliptical core) first demonstrated by Xie et al in 1986 [38]. In 2007, Jewart et al demonstrated the Bragg grating sensing characteristics of a side-hole fiber with large airholes [39]. The high transverse line load sensitivity of 176 pm/(N/mm) that was reported for the peak separation shows that optimizing the transverse sensitivity of optical fibers is possible with an adapted cross-section.…”
Section: Optical Fiber Pressure Sensorsmentioning
confidence: 99%
“…homogenized average properties which can be measured experimentally) can be assumed to be linear anisotropic if deformation is small and both materials are within the linear region. Full characterization of the effective material properties of the heterogeneous composite structure can be addressed using a series of static FEA solutions [49].…”
Section: Proposed Pressure Sensing Conceptmentioning
confidence: 99%